Perancangan SIM Klinik Bagian Kodefikasi Klinis Menggunakan Metode Waterfall Di Klinik X Kabupaten Malang - Aini, Nita Dwi Nur; Sigit, Nanta (Politeknik Negeri Jember, 2024)
Data processing, particularly in the medical record coding section, is still conducted manually using Excel, which contains lists of disease and procedure codes for coding purposes. The main issues encountered include time-consuming processes and the generation of inaccurate codes that are too general and lack specificity. The aim of this study is to design a Clinical Coding Module for the SIM Klinik system at Clinic X in Malang Regency. This research employs a descriptive quantitative method with a case study approach. A total of five doctors participated as respondents, and data was collected through interviews and observations. The study results indicate that the key features required for the SIM Klinik clinical coding module include diagnosis coding, procedure coding, and generating reports on the most common diseases. Additionally, the system must support integration with other health information systems to facilitate seamless information flow between clinic units. The system design employs a Data Flow Diagram (DFD) and Entity Relationship Diagram (ERD) approach to illustrate clear data flows and the relationships between entities in the system, ensuring that all system components function cohesively and efficiently